Audit Information Technology Using COBIT 5 in the Procurement Service Unit (Case Study: SIM UKPBJ Kabupaten XYZ) (Journal of Advances in Information Systems and Technology, 2022)
Information Technology (IT) in this all-digital era affects all aspects of human life. Including the field of government. One of them is in the Goods/Services Procurement Section of XYZ Regency, an example of an agency that has implemented IT Governance using the Goods/Services Procurement Service Unit Management Information System (SIM UKPBJ) to integrate existing operational activities. SIM UKPBJ is a means to achieve organizational goals and simplify every process in procuring goods/services. In the UKPBJ SIM, since its inception in form until now, there has never been an evaluation process regarding IT Governance that has been implemented. COBIT 5 is a framework that has a comprehensive scope starting from management and Governance. The COBIT framework is following the current state of SIM UKPBJ, 5 domains have been selected that focus on DSS05 (Manage Security Services), DSS06 (Manage Business Controls), APO11 (Manage Quality), APO12 (Manage Risk), and APO13 (Manage Security). This study used a data collection process through interviews, observations, and questionnaires. Based on the results of the study, the capability level value of each process in the DSS05, DSS06, APO11, APO12, and APO13 domains is at level 4, the predictable process and the maturity level results have an average percentage of 80.5%, namely L (Large achieved). SIM UKPBJ chooses the target level to be performed as 5, namely the Optimizing process. It is necessary to increase the capability level from the current conditions in terms of growing activities with recommendations, namely maximizing policies that are already running well and making innovations in activities to accelerate the achievement of agency goals.